Performance Evaluation of Pump and Specific Energy Consumption (SEC) in a Seawater Reverse Osmosis (SWRO) Desalination System - Suwarno, Devina Qinthara Siti Zulfaa; Bambang Puguh Manunggal; I Made Wiwit Kastawan (E-Journal Universitas Malikussaleh, 2026)
Seawater holds immense potential as a water resource in the region; however, its high Total Dissolved Solids (TDS) content—ranging from 35,000 to 45,000 ppm—renders it unsuitable for direct use. According to the World Health Organization (WHO), potable water must have a TDS level below 500 ppm. Consequently, desalination technologies have emerged to convert seawater into usable water. One such method is Sea Water Reverse Osmosis (SWRO), which is implemented by a company located in the Badung region of Bali. The SWRO initiative has received substantial support as a solution to address water scarcity, prompting this study to analyze its operational performance as a reference for future developments. The process begins with raw seawater undergoing pre-treatment, reverse osmosis, and post-treatment stages. A process flow diagram is constructed to map the flow rate across components. The primary components of the SWRO system are the High Pressure Pump (HPP) and the Reverse Osmosis (RO) membrane. The performance of the HPP is evaluated based on the ratio between hydraulic energy output and electrical energy input, while the Specific Energy Consumption (SEC) is calculated for the pump components throughout the process. For the RO membrane, the focus is placed on recovery rate and reflux ratio. The results show that the HPP achieves an efficiency of 74%, compared to the standard value of 78%. The system’s SEC is 2.58 kWh/m³, which lies within the acceptable range of 2.5–4.0 kWh/m³. The membrane demonstrates a recovery rate of 47%, aligning with the standard range of 40–50%, and a reflux ratio of 1.06, slightly below the optimal range of 1.2–1.5. Keywords: SWRO, High Pressure Pump (HPP), Specific Energy Consumption (SEC), recovery rate, reflux ratio.